Retraction Notice to: “A Discourse Analysis of German Fairy Tale “Rapunzel” Written by the Brothers Grimm” - Andi Tenrisanna Syam (Ethical Lingua: Journal of Language Teaching and Literature, 2019)
This articles initially was published in Ethical Lingua, Volume 5 Number 2, August 2018, on page 219. After careful consideration, this article has been retracted due to double publication found at https://journal.unnes.ac.id/nju/index.php/LC/article/view/14943. Apologies are offered to readers since this act of publishing misconduct was not detected during the submission process.